Doping engineering and functionalization of two-dimensional metal chalcogenides. Issue 1 (24th August 2018) - Luo, Peng; Zhuge, Fuwei; Zhang, Qingfu; Chen, Yuqian; Lv, Liang; Huang, Yu; Li, Huiqiao; Zhai, Tianyou
Abstract : In this review, we present an in-depth discussion of the state-of-the-art doping engineering and functionalization of 2D metal chalcogenides for finely tuned material properties and functions in numerous application fields. Abstract : Two-dimensional (2D) layered metal chalcogenides (MXs) have significant potential for use in flexible transistors, optoelectronics, sensing and memory devices beyond the state-of-the-art technology. To pursue ultimate performance, precisely controlled doping engineering of 2D MXs is desired for tailoring their physical and chemical properties in functional devices. In this review, we highlight the recent progress in the doping engineering of 2D MXs, covering that enabled by substitution, exterior charge transfer, intercalation and the electrostatic doping mechanism. A variety of novel doping engineering examples leading to Janus structures, defect curing effects, zero-valent intercalation and deliberately devised floating gate modulation will be discussed together with their intriguing application prospects. The choice of doping strategies and sources for functionalizing MXs will be provided to facilitate ongoing research in this field toward multifunctional applications.